Implementasi Kebijakan Model Online School di Pesantren Modern Pada Masa Pandemi - Asep Abdul Aziz; Supiana Supiana; Qiqi Yuliati Zakiah (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2021)
This study aims to analyze the policy of teaching and learning activities carried out at IHAQI Creative Boarding School Bandung. This research uses a qualitative method, in collecting information and data on the use of observation techniques and interviews online. The results of the research found that the implementation of the policy of teaching and learning activities during this pandemic has been implemented three learning models, namely (1) Model Online School (2) Model Online School and Daurah (3) Model Boarding School and Daurah. In line with the increasing development of covid-19, the headmaster determined the policy of teaching and learning activities using the online school model, this model becomes a more effective first choice. The learning used in this online school model uses media such as zoom, google classroom, google meet, and IHAQI E-Learning application. This policy is established in order to create security and protection for all stakeholders in pesantren environment because health is the main capital in carrying out healthy learning activities.